: - Khotimah, Khusnul (EDUCATIVA, 2023)
Islam Nusantara reflects Islam that is polite, friendly, tolerant and integrated with Indonesian cultural civilization. So it can be interpreted that Islam Nusantara is a concept that combines Islamic teachings (Al-Qur'an and Hadith) with culture and an archipelago perspective in the form of polite, peaceful and tolerant Islam. Understood in Idhofah terms, Islam Nusantara is structured in Arabic as Islam fii Archipelago, but the existing fii is transparent or invisible. So that it can be interpreted that Islam Nusantara is the application of Islamic teachings by Muslims in the archipelago, while Islamic teachings are the same Islamic teachings as other Islamic teachings. So that the meaning of Nusantara Islamic values here is everything that is good, important, desirable and deemed appropriate in accordance with Islamic teachings and the local culture of the Indonesian nation (Archipelago). Values are at the heart of every culture. In this case, it includes moral values that regulate the rules in living together. Moral itself experiences development that begins early. A person's moral development is very important for the personality and social development of children, for that moral education will more or less influence attitudes or behavior when interacting with other people.